Semiotics Analysis of Tempo and Gatra Magazine Cover for September 2020 Edition - Karina Kusuma WIjaya; Ruslan Ramli; Sumartono Sumartono (UIR Press, 2022)
This study discusses symbols or signs related to the coronavirus (Covid-19) pandemic that are found on the covers of Tempo and Gatra magazines edition September 2002. The two magazines has front cover to show the pandemic situation in Indonesia. At the time Indonesia was in a very serious pandemic with a number of victims every day both ordinary people or medical officer. The purpose of this study is to determine the meaning contained on cover of Tempo and Gatra by using semiotics analysis of the Charles Sanders Peirce model. It consists of three points namely sign, object, and interpretant. The research method uses a descriptive qualitative approach. The data obtained in this study were sourced from documentation and literature study such as books, literatures, notes, and a number of other related websites. The result of the research is they differ each other. Tempo tries to portray The Minister of The Health of Republic of Indonesia Terawan Agus Putranto as a character who has fun and takes unilateral advantage of the policies he makes. While on the cover of Gatra, Terawan Agus Putranto is described as overwhelmed and incompetent in fulfilling his duties as minister of health.